(untitled) (Al-Aasar, 2025)
The Holy Qur’an transcends a simple book of commands, representing an inexhaustible source of divine wisdom containing profound inner truths and spiritual insights uniquely revealed across generations. It simultaneously engages human intellect, heart, and soul, persuading reason, illuminating the heart, and guiding the soul towards closeness to Allah. This multifaceted nature has continually inspired deep exploration.Among the interpretive traditions developed is Tafsīr Ishārī (spiritual exegesis). This approach moves beyond the Qur’an’s outward dimensions (like legal rulings and linguistic analysis) to uncover subtle inner secrets and spiritual perceptions that nurture the inner being. Its core purpose is elevating humanity from preoccupation with the created world towards realizing Absolute Reality. This is achieved by aligning outward actions with Sharī‘ah (sacred law), purifying the inner self through Ṭarīqah (spiritual path), and striving for Ḥaqīqah (direct apprehension of Divine Truth), ultimately leading to true ma‘rifah (gnosis) of Allah.Rooted in Islam’s earliest generations, the scope of Ishārī Tafsīr has broadened over centuries and will continue evolving. This study emphasizes how the Qur’an’s manifest and hidden dimensions serve as an enduring guide for intellectual, ethical, and spiritual transformation.